Production of red fluorescent protein (mCherry) in an inducible E. coli expression system in a bioreactor, purification and characterization - Kuduğ, Hülya; Ataman, Bahadır; İmamoğlu, Rizvan; Düzgün, Duygu; Gökçe, İsa; İmamoğlu, Rizvan (International Advanced Researches And Engineering Journal, 2018)
New and improved genetic engineered variants of fluorescent proteins (FPs) have become useful tools for bioimaging in biomedical researches. Red fluorescent proteins (RFPs) first derived from the sea anemone Discosoma show high performance in vivo labeling and imaging. mCherry is a member of RFPs which has very high photostability, resistant to photo bleaching and rapid maturation. These advantages ensure that mCherry can be successfully fused to many proteins and widely used for quantitative imaging techniques. In this study, the constructed recombinant plasmid pBADCherry was expressed in Escherichia coli BL21(AI) then culture conditions, inducer concentration and induction time were optimized. Results of sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) analysis demonstrated that 5 hours induction at 0.04% of arabinose concentration was optimal for the highest mCherry yield. The expression of hexa histidine-tagged (6xHis) recombinant mCherry was induced by arabinose and purification performed using nickel (Ni2+) affinity chromatography. High throughput expression of 81 mg fluorescent protein from a liter of E. coli culture carried out in bioreactor.
Keywords: Bioreactor; E. coli; Fluorescent proteins; mCherry; pBAD